ON THE TOTAL IRREGULARITY STRENGTH OF CYCLES AND PATHS - CORAZON MARZUKI (NIM: 20110008), CORRY
The vertex irregular total labeling and the edge irregular total labeling were introduced by Baca, Jendrol, Miller, and Ryan in (4). Combining both of these notions, in this paper we introduce a new irregular total labeling, called totally irregular total labeling which is required to be both vertex and edge irregular. The minimum k for which a graph G has a totally irregular total k-labeling is called the total irregularity strength of G. In this paper, we provide an upper bound and a lower bound of the total irregularity strength of a graf. Besides that, we determine the total irregularity strength of cycles and paths.